2021
DOI: 10.1155/2021/8863210
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Corticosteroid Injection during COVID-19 Pandemic in Sabah: Is It Safe?

Abstract: Musculoskeletal corticosteroid injection is commonly used as an adjunct to help patients in pain management. In this current COVID-19 pandemic, many clinicians would differ from this treatment as steroid is considered an immunosuppressive drug and could risk the patient of developing severe adverse effects if contracting COVID-19. This is a retrospective study based in Sabah, Malaysia, examining the prevalence of COVID-19 infection following musculoskeletal corticosteroid injection from 1 December 2019 until 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…A recent literature review showed that only two studies have been published to determine the safety of corticosteroid injections during the COVID-19 pandemic. 1 , 3 Mohamad et al 1 conducted a retrospective study at the sports medicine clinic and the orthopaedic clinic in Queen Elizabeth Hospital and Queen Elizabeth II Hospital, in the state of Sabah, Malaysia, between 1 st December 2019 and 30th June 2020. This study enrolled 35 patients, and these were given triamcinolone as a steroid injection with a dose of 20 mg for fingers and 40 mg for other body areas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent literature review showed that only two studies have been published to determine the safety of corticosteroid injections during the COVID-19 pandemic. 1 , 3 Mohamad et al 1 conducted a retrospective study at the sports medicine clinic and the orthopaedic clinic in Queen Elizabeth Hospital and Queen Elizabeth II Hospital, in the state of Sabah, Malaysia, between 1 st December 2019 and 30th June 2020. This study enrolled 35 patients, and these were given triamcinolone as a steroid injection with a dose of 20 mg for fingers and 40 mg for other body areas.…”
Section: Discussionmentioning
confidence: 99%
“…This study enrolled 35 patients, and these were given triamcinolone as a steroid injection with a dose of 20 mg for fingers and 40 mg for other body areas. 1 Patients were then contacted via telephone and enquired about COVID-19 symptoms, and about attendance to clinics or hospitals for COVID-19 screening. 1 None of the patients developed any COVID-19 symptoms following steroid injection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations